Irrigation suction therapy reduces post-hysterectomy surgical site infection in middle-aged and older diabetic women: a randomized prospective study - Saaqib, Shazia; Naheed, Munazza (Journal of the Pakistan Medical Association, 2023)
Objective: To determine whether or not closed wound irrigation and suction therapy can reduce post-hysterectomy surgical site infections in middle-aged diabetic women without increasing pain, causing complications or lowering patient satisfaction. Method: The prospective randomised controlled study was conducted from April 2017 to March 2022 at Lady Willingdon Hospital, Lahore, Pakistan, and comprised women aged >40 years with body mass index >25kg/m2 who were scheduled for hysterectomy. The subjects were randomised into intervention group A and control group B. In the irrigation and suction group A, subcutaneous drains were inserted for daily closed wound saline irrigation followed by full-day suction for 3 days. In control group B, wound closure was done without drains and irrigation and suction. Wounds were assessed daily during hospitalisation and at 4, 8 and 12 weeks postoperatively. Primary outcome was surgical site infection rate, fever, white blood cell count, pain score and length of hospital stay. Secondary outcomes were readmission rate, wound pain during follow-up other complications and patient satisfaction. Data was analysed using SPSS 20. Results: Of the 334 patients, 300(89.8%) were included; 150(50%) in group A with mean age 56.66±9.264 years, and 150(50%) in group B with mean age 55.77±9.394 years. However, the study was completed by 274(91.3%) subjects; 138(50.4%) in group A and 136(49.6%) in group B. Group A had significantly fewer surgical site infections (p<0.0001), lower white blood cell count (p<0.0001), fever (p<0.001) and pain scores (p<.0001), shorter hospital stay (p<.0001) and higher patient satisfaction (p<.0001) compared to group B. Follow-up pain scores and other complications did not differ significantly between the groups (p>0.05). Conclusion: Irrigation and suction strategy reduced surgical site infection rates without increasing pain, causing complication or compromising patient satisfaction. Key Words: Surgical site infection, Elderly, Diabetic women, Abdominal hysterectomy, Suction, Irrigation, Satisfaction.